Satisfação habitacional da pessoa idosa: construção de instrumento e validação de conteúdo - Olaia, Leticia Felice (2023)
It is in cities that most people have aged. Research that investigates the built environment, social functions and the relationship between human beings and housing is essential. Housing, offered and guaranteed with quality, helps to prevent diseases and disabilities throughout the life cycle. Due to the great impact that housing has on people's health and quality of life, the term residential satisfactory emerged in the area of environmental psychology, with the aim of achieving measures to evaluate the space in which one lives and offer improvements, qualifying the spaces. In view of the gaps identified in the science dealing with the subject, the objective of the study is to contribute to the creation of an instrument to measure the satisfaction of elderly people in relation to their experience and carry out the validation of its content. It is a cross-sectional research, with the quantitative and qualitative method of investigation. For the content validation of the instrument, the e-Delphi method was used, an investigation technique, investigated by the possibility of joining different opinions of several specialists and building a product on complex themes, through the consensus of those involved. This research constituted a committee of specialists formed by ten professionals, selected in order to provide a heterogeneous group, interconnected by similar areas. As this is content validation through a group consensus of specialists, a Content Validation Index (CVI) equal to or greater than 80% was established. The results of the first round of instrument judgment indicated that, according to the experts, 85% of the items were considered relevant and pertinent to the proposed construct. However, some items did not reach the minimum consensus value, requiring revision and a second round of opinion. After application and analysis of the IVC of this, there was a need for new adjustments according to the suggestions of the judges, with subsequent submission of the third phase. After analysis of the third round of evaluation, all items reached the degree of agreement between the experts. In general, the research findings demonstrated the viability of the construct, being considered relevant and adequate to measure the housing satisfaction of the elderly population, simultaneously permeating objective and subjective approaches and connecting issues related to the surroundings, building and resident singularities. The study corroborated the literature regarding the dimensions that influence satisfaction, such as housing characteristics, infrastructure, public facilities, neighborhood facilities and social environment. It was also concluded that the e-Delphi method has favorable aspects in relation to its application, such as economic viability and unfavorable aspects such as the withdrawal of members of the expert committee during the instrument's evaluation rounds. As much as the proposed instrument quantitatively assesses housing satisfaction, it is pertinent to apply it together with qualitative questions in order to strengthen the investigation of this subjective construct.